Not clawing the hand that feeds you: The case of co-opted boards and clawbacks - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2019)
We examine how board co-option, defined as the fraction of the board comprising directors appointed after the CEO assumed office, is related to clawback adoption. We find that co-opted boards have a lower probability of adopting clawback provisions. Further, the negative association between board co-option and clawback adoption is more pronounced when at least one co-opted member is on the compensation committee and when there is a higher likelihood that a clawback provision will be triggered. Finally, we find that board co-option is an important mechanism through which longer-tenured CEOs reduce the likelihood of clawback adoption.